(3JaVjd GdCJQGc Ydi SGFQ GdCLfGO hefGbH GdMVQI GdYGdjI GdSdWGfjIs - (3CHh GdYdGA eMeO Hf Ydj Hf GdMSf Hf MShd,J (B450 (3g` s
(3ChdgG (B:s
(3PcQJ CHbGc Gddg GdcJGH GdeYQha HGdJGLi dEHQGgje Hf gdGd GdUGHi heGQGbc ef eMGSf daXg , hHOGFY Qbeg s
(3BNQgG (B:s
(3hCQLY Edi GdCLd YejO Gdedc cJH Gddg dg ajeG Yfg ef BKGQg dHYOg Yf SGei HGHg s
(3YGQVgG HGdCUd GdMSf Hf eMeO GdUZGfi SfI (B649(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B276s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B553 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B118 s
Keywords: (3GdJGQjNs